2001
DOI: 10.1126/science.1057759
|View full text |Cite
|
Sign up to set email alerts
|

Solar Forcing of Drought Frequency in the Maya Lowlands

Abstract: We analyzed lake-sediment cores from the Yucatan Peninsula, Mexico, to reconstruct the climate history of the region over the past 2600 years. Time series analysis of sediment proxies, which are sensitive to the changing ratio of evaporation to precipitation (oxygen isotopes and gypsum precipitation), reveal a recurrent pattern of drought with a dominant periodicity of 208 years. This cycle is similar to the documented 206-year period in records of cosmogenic nuclide production (carbon-14 and beryllium-10) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
349
1
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(395 citation statements)
references
References 30 publications
26
349
1
11
Order By: Relevance
“…These are superimposed on a period of generally lower Ti content. Not counting the duration of the more severe multiyear droughts, the number of varves between drought events indicates a spacing of ~40 to 47 years (± 5), a number that agrees remarkably well with the observation of subpeaks at about 50-year intervals in the wellknown Lake Chichancanab sediment density record (Hodell et al, 2001). …”
Section: Referencessupporting
confidence: 81%
See 1 more Smart Citation
“…These are superimposed on a period of generally lower Ti content. Not counting the duration of the more severe multiyear droughts, the number of varves between drought events indicates a spacing of ~40 to 47 years (± 5), a number that agrees remarkably well with the observation of subpeaks at about 50-year intervals in the wellknown Lake Chichancanab sediment density record (Hodell et al, 2001). …”
Section: Referencessupporting
confidence: 81%
“…It has been suggested that recurrent patterns of drought played an important role in the complex history of the Maya (Hodell et al, 2001;Gill, 2000). Maya civilization developed in a seasonal desert and was highly dependent on a consistent cycle of rainfall to support agricultural production.…”
Section: Referencesmentioning
confidence: 99%
“…This has been observed in 14 C from trees growing in Panama (Westbrook et al, forthcoming) and in Thailand (Hua et al 2002). Evidence for migration of the ITCZ on multi-decadal to millennial time scales has been seen in proxy records from around the globe (Arz et al 1998;Haug et al 2001;Hodell et al 2001;Luckge et al 2001;Marret et al 2001;Maslin and Burns 2000;Wang et al 2004). It is beyond the scope of IntCal to determine the location of the paleo-ITCZ, but those who wish to develop chronologies for records in this region should be aware of this complication.…”
Section: Discussionmentioning
confidence: 77%
“…Solar activity has been shown to influence key components of the climate system, such as temperature, winds, precipitation, ocean circulation and iceberg transport (e.g. Verschuren et al, 2000;Bond et al, 2001;Hodell et al, 2001;Andrews et al, 2003;Jiang et al, 2005;Sejrup et al, 2010;Martin-Puertas et al, 2012;Knudsen et al, 2014;MoffaSanchez et al, 2014a;Jiang et al, 2015). However, only a few studies have investigated the link between variations in sea-ice proxies from the North Atlantic and solar variability on multidecadal to centennial time scales (e.g.…”
Section: Introductionmentioning
confidence: 99%